Femtosecond nonlinear optical properties of lead-germanium oxide amorphous films - Rativa, Diego; de Araujo, Renato E.; de Araujo, Cid B.; Gomes, Anderson S. L.; Kassab, Luciana R. P. (American Institute of Physics (AIP), 2007)
The nonlinear (NL) response of lead-germanium oxide amorphous films was investigated using a Ti:saphire laser delivering pulses of approximate to 150 fs at 800 nm. The Kerr shutter technique was employed to reveal the time response of the nonlinearity that is smaller than 150 fs. The sign and magnitude of the nonlinearity were obtained using a novel technique called thermally managed eclipse Z scan which allows the simultaneous characterization of cumulative and noncumulative NL effects. The NL refractive index of electronic origin, n(2)approximate to 2x10(-17) m(2)/W, and the NL absorption coefficient, alpha(2)approximate to 3x10(3) cm/GW, were determined. (c) 2007 American Institute of Physics.